The Economics of Illusion; A Critical Analysis of Contemporary Economic Theory and Policy - Froehlich, Walter; Hahn, L. Albert (The Review of Economics and Statistics, 1950)
should be identified with social control of the rate and direction of progress, not with the absence of progress (p. I6o, italics added). Lauterbach himself admits that this cannot mean an absolute individual security. But even so I do not feel that the effects of expansion in causing both unexpected change and personal insecurity are at all adequately appreciated. Nor does Lauterbach relate his emphasis on the non-material drives (p. I63) to the pressure group problems which change involves in any society. Scientific discovery is taken as more or less automatically self-implementing, within the plan, despite pressure groups. Finally, Lauterbach's political analysis seems fundamentally incomplete. It is greatly to his credit that he does not rely on mere elections to maintain freedom. Nevertheless, except for emphasis on elections and on the need for a good moral attitude taken by intelligent and educated voters, there is little of a constructive nature to be found in his treatment. He does not seem to have fully realized that, unless the voters have some economic independence, an election will tend to become a farce. Also, the role of competing employment opportunities in helping to underwrite such independence, and in facilitating the rise of independent leadership and discovery, is largely overlooked. On all these points I would like to refer the reader to my Democracy and Progress. Leaving aside political na-vete, the fundamental defect of the book is the lack of any coherent theory of social growth and economic development. If Lauterbach were advocating a stationary society he would be on much stronger ground economically at least. We could then combine decentralized planning with literal personal (economic) security. But Lauterbach specifically wants a higher standard of living, and it is just here that his analysis is most inadequate. However, not everyone believes in a growing society, and it is worth asking whether, even if we decided on a stationary state, it could be kept politically free. I do not think so. How would people be stopped from trying out new ideas unless there were established drastic social penalties for innovation, or some sort of inquisition for the suppression of dangerous thoughts? In short, the basic problem seems to me to be that if we make men genuinely free they become creative, and that if they become creative they simultaneously create growth and insecurity. No technique of planning can ever wholly overcome this difficulty, and while a workable compromise is certainly possible there is always the danger that as we cut down on the insecurity we may find ourselves cutting down on the growth. One can find these conclusions in Lauterbach, but not entirely with the author's help.